Impact of the Brazilian Low-Carbon Agriculture Program on recovery of degraded pastures and milk production - Pinto, Bruno Chaves Morone (2020)
This research aimed to analyze the effect of the ABC Program's recovery of degraded pastures subprogram on milk production and animal stocking rate in the treated municipalities. The animal stocking rate is utilized as a proxy for degraded pastures, as there is a positive relationship between animal stocking rate and pastures quality (DIAS-FILHO, 2011). In addition, this work aimed to verify the distribution of the funds of this subprogram, as well as the distribution of the milk production and animal stocking rate in the Brazilian territory. The hypothesis of this research is that the credit for recovering of degraded pasture had a positive effect on municipal milk production, as well as it elevated the animal stocking rate. Since there is availability of data in the pre and post-treatment periods, it was utilized the differences-in-differences method, in conjunction with Entropy Balancing. The idea is to match treated municipalities with the control municipalities that presented similar characteristics (milk production, animal stocking rate, socioeconomic variables and climatic characteristics) before the Program. Moreover, in order to analyze whether the effect varied between the municipalities in different distribution of animal stocking rate and milk production, it was utilized the Quantile Regression, using the 25", 50" and 75" quantiles. The data if milk production and animal stocking rate are from da Produção Agrícola Municipal (PAM — IBGE), the socioeconomic and climatic controls were extracted from IBGE (2018) and Xavier, King and Scanlon (2017), respectively. Data of ABC credit and other types of credit were extracted from SICOR (2019). The results presented that the distribution of the funds of the ABC Program's recovery of degraded pasture subprogram concentrated in the Midwest and in Matopiba regions. Furthermore, the result provided signs that the credit of ABC Program's recovery of degraded pastures has increased the milk production of the treated municipalities. The results maintained positive even after the inclusion of the climate and economic variables. However, there is no evidence of the existence of larger effects in municipalities that receive credit in more than one year when compared to those which were treated by the program once. In addition, the effects remained positive and statistically significant at 25th, 50th and 75th percentiles, even though was not observed differences in the effect between the percentiles. On the other hand, it was not possible to conclude whether there was effect of the credit on animal stocking rate in the treated municipalities. In fact, the results presented that the effect of the ABC Program on animal stocking rate was not Statistically significant in the year of the first-time treatment. Further, it was observed a negative effect of the credit on animal stocking rate in the second and third-treatments periods. Keywords: ABC Program. Recovery of degraded pastures. Milk production. Animal stocking rate.